Vitamin D status and risk of metabolic syndrome among non-diabetic young adults. Issue 3 (June 2015) - Huang, Chiao-Yu; Chang, Hao-Hsiang; Lu, Chia-Wen; Tseng, Fen-Yu; Lee, Long-Teng; Huang, Kuo-Chin
Summary Background and aims Low vitamin D status has been linked to obesity, insulin resistance, and metabolic syndrome. In the present study, we aimed to explore the nature and strength of the relationship between vitamin D and metabolic syndrome among non-diabetic young adults. Methods This was a campus-based cross-sectional study of 355 non-diabetic young adult graduate students (233 males and 132 females; mean age, 23.5 ± 2.4 years) in Northern Taiwan. We measured and tested the association of serum 25-hydroxyvitamin D levels with metabolic syndrome and cardio-metabolic parameters. Results A total of 24 (6.8%) recruited young adults had metabolic syndrome. There were decreasing trends of body mass index (BMI), Homeostasis Model of Assessment-Insulin Resistance (HOMA-IR) and prevalence of metabolic syndrome across increasing tertiles of vitamin D levels irrespective of age and sex (P for trend <0.05). Without adjusting for BMI or HOMA-IR, the odds of having metabolic syndrome decreased across increasing tertiles of vitamin D levels (P for trend 0.021). The odds ratio of having metabolic syndrome was 0.26 (95% confidence interval: 0.08–0.85, P = 0.025) for the highest vs. the lowest tertile of vitamin D levels. However, further adjustments for BMI and HOMA-IR largely removed the inverse association of vitamin D status with metabolic syndrome and its individual components. Conclusion Among non-diabetic young adults, the potential inverse relationship between vitamin D status and metabolic syndrome may be attributable to the conjunctive effects of individual obesity and insulin resistance.